Aberrations of Genomic Imprinting in Glioblastoma Formation - Lozano-Ureña, Anna; Jiménez-Villalba, Esteban; Pinedo-Serrano, Alejandro; Jordán-Pla, Antonio; Kirstein, Martina; Ferrón, Sacri R. (Frontiers in Oncology, 2021)
IIn human glioblastoma (GBM), the presence of a small population of cells with stem cell characteristics, the glioma stem cells (GSCs), has been described. These cells have glioblastoma potential and are responsible of the origin of the tumours. However, whether GSCs originate from normal neural stem cells (NSCs) in consequence of genetic and epigenetic changes and/or dedifferentiation from somatic cells remains to be investigated. Genomic imprinting is an epigenetic marking process that causes genes to be expressed depending on their parental origin. The dysregulation of the imprinting pattern or the loss of genomic imprinting (LOI) have been described in different tumours including GBM, being one of the earliest and most common events that occurs in human cancers. Here we have gathered the current knowledge of the role of imprinted genes in normal NSC function and how the imprinting process is altered in human glioblastoma. We also review the changes at particular imprinted loci that might be involved in the development of the tumour. Therefore, understanding the mechanistic similarities in the regulation of genomic imprinting between normal NSCs and GBM cells will be helpful to identify molecular players that might be involved in the development of human glioblastoma.